Potassium fertilization in peach fruit quality - Barreto, Caroline Farias; Ferreira, Letícia Vanni; Navroski, Renan; Benati, Jorge Atílio; Cantillano, Rufino Fernando Flores; Vizzotto, Marcia; Nava, Gilberto; Antunes, Luis Eduardo Correa (Revista de Ciências Agroveterinárias, 2020)
For peach trees produced in southern Brazil, information about the influence of potassium fertilization on fruit quality remains scarce. This study set out to determine the physicochemical properties and bioactive compounds of peaches treated with different doses of potassium applied to the soil for three consecutive crop years. The experiment examined the Sensação cultivar in a commercial orchard in the municipality of Morro Redondo, Rio Grande do Sul, Brazil, during the 2016, 2017, and 2018 crop years. Peach trees of the Sensação cultivar were fertilized with potassium (K); doses of 0, 40, 80, 120, and 160 kg ha-1 of K2O in the form of potassium chloride were applied to the soil surface. After harvest, an assessment was made of the soluble solids (SS) content, titratable acid (TA) content, SS/TA ratio, pH levels, flesh color, skin and flesh firmness, total carotenoid content, total phenolic content, and antioxidant activity. The peaches’ skin firmness, SS/TA ratio, and concentration of carotenoids responded to potassium fertilization, but only in some production cycles. Their color, flesh firmness, soluble solids, juice pH levels, total phenols, and antioxidant activity did not change with the application of potassium in the soil.